Invitations and Incentives for Primary Care Screenings in Armenia - World Bank (World Bank, Washington, DC, 2020)
Since 2011, the Armenian government has implemented a national performance-based financing scheme which has given financial incentives to providers for screening the population, including for hypertension and diabetes. In addition, there have been investments in training health workers on clinical guidelines and mass media campaigns to increase demand. Personal invitations from family physicians prompted users to consider their need for screening, but attendance also depended on the personal value on one’s health and the perceived health benefits of screening. Global experience indicates that conditional financial incentives can increase preventive health care use by removing resource constraints to adopting healthy behaviors and by helping overcome issues of bounded rationality or willpower. Messaging interventions, including mass media messages and personal invitations, can also increase preventive health care use by reducing obstacles to change, adjusting perceptions of social norms, or associating the desired behavior with valued outcomes.This study estimates the impact of demand-side financial incentives and invitations from a family physician on primary care screening attendance rates and examines potential mechanisms of action.